2017
DOI: 10.18393/ejss.303512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil fertility status of Regional Agricultural Research Station, Tarahara, Sunsari, Nepal

Abstract: Article Info

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
7
15
0
Order By: Relevance
“…Soil pH varied from strongly acidic (< 5.5) in 21.12% to strongly alkaline (> 7.8) in 2.48% of the total area ( Table 4 and Fig 2 ). These results are in agreement with those reported in a recent study of soils of the Terai region [ 22 , 45 ]. The variation in soil pH could be attributed to the nature of the alluvial parent material, micro topography, and the type and history of fertilizer used [ 46 ].…”
Section: Resultssupporting
confidence: 94%
“…Soil pH varied from strongly acidic (< 5.5) in 21.12% to strongly alkaline (> 7.8) in 2.48% of the total area ( Table 4 and Fig 2 ). These results are in agreement with those reported in a recent study of soils of the Terai region [ 22 , 45 ]. The variation in soil pH could be attributed to the nature of the alluvial parent material, micro topography, and the type and history of fertilizer used [ 46 ].…”
Section: Resultssupporting
confidence: 94%
“…Similiarly, Sheykhbaglou et al (2010), Nadi et al (2013) and Singh et al (2017) reported that nano Fe particles have beneficial effects on plant growth criteria and grain yield in soybean and fababean, respectively. Previous researches showed that nano fertilizers lead an increase in the use efficiency of plant nutrients, reduce soil toxicity, decrease the potential adverse effects of excessive chemical fertilizer use and fertilizer application frequency (Brunner et al, 2006;Khadka et al, 2017). Nano fertilizers have large surface area and particle size less than the pore size of root and leaves of the plant which can increase penetration into the plant from applied surface and improve uptake and nutrient use efficiency of the nano fertilizer (Liscano et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Rameshaiah et al (2015) reported that excessive doses of nano materials used in agricultural lands may be cause hazardous effects on living organisms and human health. The selection and cultivation of iron toxicity tolerant genotype may be another suitable option for its toxicity management (Khadka et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…From 1971 to 2014, the average minimum and maximum temperatures of 18.6 and 30.1°C with an average annual rainfall of 1794.3 mm were recorded for this site (DHM 2017). Khadka et al (2017) reported that the soil at the Tarahara site was moderately acidic in nature, and the organic matter (2.80 ± 0.07%) contained 30.32% sand, 48.92% silt, and 20.76% clay.…”
Section: Study Sitesmentioning
confidence: 99%